Nonparametric Estimation of a Dependent Competing Risks Model for Unemployment Durations - Gerard J. van den Berg; A. Gijsbert C. van Lomwel; Jan C. van Ours (Institute for the Study of Labor (IZA), 2003)
In this paper we simultaneously analyze transitions from unemployment to employment and to nonparticipation. We estimate a dependent competing risks model with nonparametric specifications of the destination-specific duration dependence and unobserved heterogeneity terms. We use a unique population data set of French unemployment over the period 1988-1994, stratified by gender type, duration class and exit state.
Keywords: J64; C41; 330; exit rate; hazard rate; unobserved heterogeneity; duration dependence; nonparticipation; Arbeitslosigkeit; Dauer; Mikroökonometrie; Nichtparametrisches Verfahren; Schätzung; Frankreich